MOVEMENTS AND RESOURCE USE BY MOOSE IN TRADITIONAL AND NONTRADITIONAL HABITATS IN NORTH DAKOTA - Maskey Jr., James J.; Sweitzer, Rick A. (Lakehead University, 2020)
In the past several decades, moose (Alces alces) have expanded their range in North Dakota from primarily forested areas to the prairie/agriculture mosaic of the state. As a result, moose are now well-established in a large portion of North Dakota, yet little is known about their ecology in the state. We examined the home ranges, habitat selection, and diets of moose in both traditional (forested) and nontraditional ranges (prairie/agricultural) and inferred whether range expansion is the result of agriculture-related landscape changes. From 2004 to 2006, we placed GPS radio-collars on a total of 14 moose in two study areas: Turtle Mountains (forested) and Lonetree (prairie/agricultural). Total and seasonal home ranges were larger for Lonetree moose, and moose in both study areas selected strongly for wooded habitat. In both study areas seasonal diets ranged from 65 to 99% woody browse, with forbs 15% of summer diets. In the Lonetree area row crops made up the second highest consumed forage in fall (12%) and winter (29%) diets. Larger home ranges in the Lonetree area may reflect the low availability and scattered distribution of wooded habitat. Further, the strong selection for planted woodlands and the high proportion of woody browse and row crops in the diet of Lonetree moose suggests that conversion of the native prairie to agriculture has facilitated range expansion by moose in North Dakota.